Social and Institutional Status of Area Exclosure in North Wollo and Waghemira Zones, Northeastern Ethiopia - Melkamu Kassaye Mekonen; Abrham Abiyu Hailu; Asmamaw Alemu Abitew (International Journal of Forestry Research)
Forest restoration with area exclosure has the hopeful restoration strategy for nature conservation and social development goals as a countermeasure against deforestation and forest degradation. However, the status of these restoration interventions is not well known with scientific evaluation. Thus, this study aimed to evaluate the social and institutional status of forest restoration with area exclosures. To do this, three districts in three agroecologies were selected purposively based on exclosure availability, and in each district, three exclosures were selected. The questionnaire survey was administered to households near the selected exclosures for both user and nonuser groups selected with simple random sampling. Required data were collected and analyzed by descriptive and inferential statistics and then compared against the best practices of Ostrom’s design principles (ODPs). The result revealed that the local community has good trust and participation in highland (63%) and mid-altitude (70%) areas, but low trust and participation in lowland areas (85%). In the highland and mid-altitude areas, local communities have the right to use exclosure for multiple uses. In lowland areas, the use right is very restricted for local communities. Exclosure institutions and governance showed medium compliance in the highland, very good compliance in mid-altitude, and very poor compliance in the lowland with the ODP. This was triangulated when 79% of the respondents in highland and 82% in mid-altitude argued that area exclosure is successful and 82% of respondents argued that area exclosure is failed in the lowland. For successful and sustainable forest restoration practice with area exclosure, the approach should start at the bottom and the activity should require the full participation of the local community in all stages.